Analyzing the Impact of Service Quality and Pricing on Customer Satisfaction: A Study at Eat Home Culinary Tabanan, Indonesia - I Made Alit Hermawan; Putu Guntur Pramana Putra; I. B. Nyoman Krisna Prawira Yuda (Pubfine Media Group, 2025)
Introduction: The culinary tourism sector serves as one of the economic pillars in Tabanan, Indonesia, encompassing various businesses such as restaurants, eateries, cafes, and catering services. EAT Home Culinary Tabanan is one such establishment contributing to this sector. This study aims to examine and provide empirical evidence regarding the influence of service quality and price on customer satisfaction at EAT Home Culinary Tabanan, Indonesia. Methods: The research was conducted using a quantitative approach with a sample of 100 respondents selected through non-probability sampling. Data were collected via questionnaires utilizing a 5-point Likert scale. The data analysis techniques included validity and reliability tests, classical assumption tests, multiple correlation and regression analysis, t-test, and F-test. All analyses were performed using SPSS version 22.0 for Windows. Results: The findings indicate that service quality (X1) has a partial effect on customer satisfaction (Y). Similarly, price (X2) also has a partial effect on customer satisfaction. Furthermore, service quality and price simultaneously exert a positive and significant influence on customer satisfaction at EAT Home Culinary Tabanan. Conclusion: Both service quality and price play important roles in enhancing customer satisfaction. Future research is encouraged to explore additional variables that may affect customer satisfaction beyond those investigated in this study.